KAJIAN BUKU AJAR SISWA DALAM PEMBELAJARAN SAINS PERSPEKTIF INTEGRASI PEMBELAJARAN SAINS DAN ISLAM MI - Vivi Afbrifani (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Abstract: This study aims to describe the content of science textbooks of class I and IV the 1st half 2013 curriculum for teachers and students based on the integration of science and Islam, and explain the patterns of integration of science and islam in the textbooks of science in Elementary School. The result showed that the content of science textbooks of class I and IV in elementary school is based on the integration of science and islam but it is not significantly. This is indicated by the amount of text its contents are still a bit of general nature, such as a quick description of almaighty God as the creator, the diversity of his creation, suggestions for ingratitute towards God and creation take advantage for a good purpose. There are six patterns of integration of science and islam in the textbooks of science in elementary school, such as similarisasi, parallelization, complementation, comparison, inductivication, and verification, however, the existing pattern in the textbooks of class I and IV semesters 1 at elementary school is only one pattern, it is induktivikasi pattern.